Disruption of hepatocyte Sialylation drives a T cell-dependent pro-inflammatory immune tone - Oswald, Douglas M.; Zhou, Julie Y.; Jones, Mark B.; Cobb, Brian A. (Glycoconjugate journal, 2020)
Through the catalysis of α2,6-linked sialylation, the enzyme ST6Gal1 is thought to play key roles in immune cell communication and homeostasis. Of particular importance, glycans with terminal α2,6-sialic acids are known to negatively regulate B cell receptor signaling and are associated with an immunosuppressive tumor microenvironment that promotes T cell anergy, suggesting that α2,6-sialic acids are a key immune inhibitory signal. Consistent with this model, mice harboring a hepatocyte-specific ablation of ST6Gal1 (H-cKO) develop a progressive and severe non-alcoholic fatty liver disease characterized by steatohepatitis. Using this H-cKO mouse, we have further discovered that loss of hepatocyte α2,6-sialylation not only increases the inflammatory state of the local tissue microenvironment, but also systemic T cell-dependent immune responses. H-cKO mice responded normally to innate and passively induced inflammation, but showed significantly increased morbidity in T cell-dependent house dust mite-antigen (HDM)-induced asthma and myelin oligodendrocyte glycoprotein (MOG) peptide-induced experimental autoimmune encephalomyelitis (EAE). We further discovered that H-cKO mice have a profound shift toward effector/memory T cells even among unchallenged mice, and that macrophages from both the liver and spleen expressed the inhibitory and α2,6-sialic acid-specific glycan binding molecule CD22. These findings align with previously reported pro-inflammatory changes in liver macrophages, and support a model in which the liver microenvironment sets a systemic immune tone that is regulated by tissue α2,6-sialylation and mediated by liver macrophages and systemic T cells.